Service Quality and the Mediating Effect of Corporate Image on the Relationship between Customer Satisfaction and Customer Loyalty in the Malaysian Hotel Industry - Cheng, Boon-Liat (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2013)
Service quality is vital to the success ofÂ any service organization. The rapid growth of the Malaysian hotel industry in the 2000âs forced hotel operators to seriously recognize the importance of service improvement in order to gain competitive advantage. This study aims to examine the impact of service quality on customer satisfaction, and how customer satisfaction subsequently affects customer loyalty in the hotel industry in Malaysia. This study also investigates the mediating effect of corporate imageÂ on theÂ relationship between customer satisfaction and customer loyalty.Â A systematicÂ sampling approach was adoptedÂ to collect data through self-administered questionnaires from 500 hotel guests. Preliminary data analysis, descriptive analysis, reliability test and regression analysis were adopted to ana-lyzeÂ theÂ reliabilityÂ ofÂ items and theÂ hypothesizedÂ relationshipsÂ in theÂ proposedÂ research model.Â The findings revealed that perception of service quality is significantly related to customer satisfaction, which in turn generates positive customer loyalty in the hotel industry. Besides, corporate image is found to be a partial mediator in the relationship between customer satisfaction and customer loyalty. Overall, the find-ings of this study would help hotel operators to formulate and implement effective marketing manage-ment strategies to cope with the keen competition in the hotel service industry.Â Â Â Â